Effect of YSZ Volume on Polarization Resistance of Anode with Magnetically Aligned Ni. (30th May 2017) - Nagato, Keisuke; Shintani, Kodai; Shikazono, Naoki; Shimura, Takaaki; Nakao, Masayuki
Abstract : Aligned yttria-stabilized zirconia (YSZ) and Ni network with large triple-phase boundaries (TPBs) is considered to be an ideal structure to improve the electrochemical performance of the solid oxide fuel cell (SOFC) anode. In our previous research, Ni alignment method using magnetic field has been proposed. Since the connectivity of Ni is guaranteed, volume ratio of YSZ is possibly increased to increase the effective ionic conductivity and durability of the anode. Although the increase of YSZ volume ratio prompts improvement of ionic conductivity, the TPB density is decreased. In this study, the effect of the YSZ volume ratio on the performance of the anode is investigated. The volume ratio of Ni and YSZ was varied as 50 : 50, 33 : 67, and 20 : 80 %. Without the magnetic field, the polarization resistance of the cell increased with the increase of YSZ volume fraction. On the other hand, with the magnetic field, the polarization resistances remained nearly unchanged regardless of the YSZ volume fraction. The microstructures were reconstructed by focused ion beam-scanning electron microscopy, and the connectivity, TPB densities, and tortuosities are investigated by a numerical simulation.